A Well-understood Surgical Informed Consent : A Scoping Review - Rieke Cahya Budi; Adik Wibowo (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
The implementation of surgical consent has shifted from simply getting a signature to a focus on doctor-patient communication. Providing adequate information is very important for patients in making decisions so that patients do not feel forced to agree. Good understanding is required before a patient gives consent, but many patients have difficulty understanding and doctors fail to provide correct information. The aim of this scoping review is to investigate and evaluate patient comprehension of surgical informed consent provided by standard procedure or other methods and factors affecting patient comprehension. Three electronic database searches (ProQuest, ScienceDirect, and Scopus) were performed from 2017 until 2022. A total of 391 articles were identified and 25 articles were selected according to the PRISMA guidelines and the PCC framework. 9 of 11 articles stated that patient understanding level was low. Factors that influence it include education level, age and language limitations. 12 studies (85%) showed that patient understanding improved with the use of additional information media. Overall patient comprehension of surgical informed consent is low. This depending on the communication between the doctor and the patient. An interesting interventions can be used to improve patient understanding of surgical informed consent